Igneous Rock Associations in Canada 3. Large Igneous Provinces (LIPs) in Canada and Adjacent Regions: 3 Ga to Present - Ernst, R.; Buchan, K. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2004)
SUMMARY Earth history is punctuated by numerous periods during which large volumes of mafic magma were emplaced. Such magmas not generated by a 'normal' spreading ridge or by subduction are termed Large Igneous Provinces (LIPs), and consist of continental flood basalts, volcanic rifted margins, oceanic plateaus, ocean basin flood basalts, submarine ridges, and seamount chains. Associated felsic rocks may also be present. LIPs of Mesozoic and Cenozoic age are typically the best preserved. Those of Paleozoic and Proterozoic age are usually more deeply eroded, and consist of flood basalt remnants and a deep-level plumbing system (of giant dyke swarms, sill provinces and layered intrusions). In the Archean the most promising LIP candidates are greenstone belts containing komatiites. Many LIPs have been linked to regional-scale uplift, continental rifting and breakup, and climatic crises. They can be used as precisely dated time markers in the stratigraphic record, and are key targets for Ni-Cu-PGE exploration. LIPs have also become a focus in the debate on the existence and nature of mantle plumes. Canada has a rich record of LIPs. At least 80 candidates are recognized in Canada and adjacent regions, with ages ranging from 3100 to 17 Ma. We review proposed links between the LIP record of Canada and mantle plumes, continental breakup, regional uplift, and ore deposits. However, given that many mafic units in Canada remain poorly characterized, a concerted geochronology campaign with integrated paleomagnetism and geochemistry would be invaluable in expanding the application of the Canadian LIP record to solving major geological problems.